Lecturer and Student Readiness on Interprofessional Teamwork Education: Quasi-Experimental Study in Health Sciences - Yuni Purwati, Suryani and Lutfi Nurdian Asnindari (International Journal of Advanced Science and Technology, 2020)
This study aims to build the attitudes and readiness of lecturers and students in learning Interprofessional Education (IPE). The type of this study was the quantitative study with a quasi-experimental method. The population and sample of this study were the lecturers and the students of the Faculty of Health Science. The sample of this study was determined through the incidental sampling technique. The number of this study was 40 lecturers and 78 students. The instruments of this study were RIPLS questionnaire, consisting of 19 questions given before and after the IPE training were given. The statistical analysis used in this study was the paired t-test. The results of the Paired Samples Test Analysis in the Lecturer group showed the Sig. 0,000 and the students scored Sig. 0.008, each smaller than 0.05. Based on the above analysis, it is concluded that interprofessional education training for lecturers and student groups has a positive impact on attitudes and readiness for the application of interprofessional education. Especially in nursing study program and nutrition science, readiness is better than other health study programs, both in the lecturer and student groups. The suggestion for Aisyiyah University of Yogyakarta was that it was able to become a driving force in the preparation of the implementation of IPE by continuing research through IPE curriculum and module feasibility study that will be applied both offline and online methods.